Constructing Police Legitimacy During Protests: Frames and Consequences for Human Rights - Dammert-Guardia, L (Routledge, 2022)
Police legitimacy is a constructed concept. Theorists argue that legitimacy is achieved through police practices that conform to the law and societal expectations, and respect human rights. The challenge is that the distinction between acceptable and unacceptable police force requires interpretation. This article uses a qualitative frame analysis of leading Chilean newspapers to reveal how police and their supporters justified police actions in response to the massive social protests in Chile from October to December 2019. We argue that the dominant frames speakers used to explain police actions during the social uprising justified police violence as a legitimate response to a criminal threat and as consistent with police protocols and the law. While reasserting police legitimacy, the frames delegitimise claims of human rights abuses (often explicitly) and shift the dominant public conversation away from discussions of broader public security and public order reforms that could better reduce police violence. Such frames reveal the tensions between police legitimacy and human rights protections, and the power of state and civil society voices elevated in the media to challenge the latter. © 2021 Informa UK Limited, trading as Taylor & Francis Group.